PREVALENCE OF CHRONIC KIDNEY DISEASE (CKD) IN PATIENTS PRESENTING WITH HYPERTENSION A RETROSPECTIVE STUDY (The Research of Medical Science Review, 2025)
Background: Chronic kidney disease (CKD) is a major global health concern, and hypertension is one of its leading causes and contributors. Early detection and intervention are critical to reducing CKD progression and associated complications, especially in resource-constrained settings like Pakistan. Objective: This study aimed to determine the prevalence of CKD among hypertensive patients and to identify key demographic, clinical, and biochemical factors associated with CKD progression. Methodology: A retrospective cross-sectional study was conducted in tertiary care hospitals of Pakistan, including 273 hypertensive patients from March 2023 to September CKD was classified using the estimated Glomerular Filtration Rate (eGFR) and Albumin-to-Creatinine Ratio (ACR) based on KDIGO guidelines. Data were analyzed using bivariate analysis (chi-square tests) and multivariable logistic regression to identify predictors of CKD. Results & Findings: Among 273 patients, 57.1% were diagnosed with CKD. The highest prevalence was observed in Stage 3 CKD (35%), followed by Stage 4 (15%) and Stage 5 (7.1%). Significant predictors of CKD included age >60 years (OR: 2.8; 95% CI: 1.9–4.0; p<0.001), diabetes (OR: 3.2; 95% CI: 2.0–5.0; p<0.01), and hypertension duration >10 years (OR: 2.5; 95% CI: 1.7–3.7; p<0.001). Biochemical analysis showed a progressive increase in ACR and a decline in eGFR with advancing CKD stages, reflecting severe renal impairment in advanced stages. Conclusion: CKD is highly prevalent among hypertensive patients, with older age, diabetes, and prolonged hypertension identified as key risk factors. Routine screening using eGFR and ACR is essential for early detection and management. Targeted interventions for high-risk groups are critical to mitigating CKD progression and its associated burden.